Digitalisasi Pelayanan Desa Mangunrejo Melalui Pengembangan Sistem Informasi Berbasis Web - Hidayatus Sibyan; Nur Hasanah; Nahar Mardiyantoro; Dimas Prasetyo Utomo; Erna Dwi Astuti; Adi Suwondo; Danie Amrie Dwi Kurniawan (AMMA : Jurnal Pengabdian Masyarakat, 2026)
The use of information technology further encourages the transformation of public services to the village government level, one of which is through the implementation of a web-based information system. However, the administrative process in Mangunrejo Village is still carried out conventionally, starting from population data management, mail services, service queue arrangements, to handling community complaints. This condition causes services to be less efficient, require longer turnaround times, and increase the risk of administrative errors. This Community Service activity aims to design and implement a web-based village service information system as a form of support for the digital transformation of village administration. The implementation of activities is carried out through several stages, namely identification of partner needs, analysis of system needs, application design, development of web-based systems, functional testing, and preparation of activity documentation. The resulting system integrates various administrative services, including citizen data management, correspondence services, queue services, and community complaint management in one platform. The results of the implementation show that the system is able to simplify administrative processes, improve the regularity of data management, and support the implementation of more effective and documented services. Therefore, the information system developed can be one of the alternative solutions in accelerating the implementation of digitization of public services in Mangunrejo Village.